Prevention of work-related decompression illness events by detection of a cardiac right-to-left shunt - Kütting, Birgitta; Tomandl, Bernd; Drexler, Hans (Scandinavian Journal of Work, Environment & Health, 2004)
A 44-year-old tunnel worker was studied who suffered from several unexplained decompression illness events for almost 15 years. This caisson worker was affected after standard pressure profiles that did not cause symptoms of decompression illness in his colleagues on the same shift. Transesophageal echocardiography revealed an atrial septal defect (grade II) in this otherwise healthy man. Cranial magnetic resonance imaging showed ischemic brain lesions. Among divers, patent foramen ovale, the most common cause of cardiac right-to-left shunts, was shown to increase the risk for decompression illness events by a factor of 4.5 and to double the risk of ischemic brain lesions. Hyperbaric workers with symptoms of unexplained decompression illness, even if they are only slight, should immediately be transferred to a cardiologist so that a cardiac right-to-left shunt will not be overlooked.
Keywords: cardiac right-to-left shunt; cardiac shunt; case report; decompression illness; occupational medicine; patent foramen ovale; prevention; professionals under hyperbaric conditions; work